A critical review in strategies to improve photocatalytic water splitting towards hydrogen production. (8th January 2019) - Fajrina, Nur; Tahir, Muhammad
Abstract: Water splitting for hydrogen production under light irradiation is an ideal system to provide renewable energy sources and to reduce global warming effects. Even though significant efforts have been devoted to fabricate advanced nanocomposite materials, the main challenge persists, which is lower efficiency and selectivity towards H2 evolution under solar energy. In this review, recent developments in photo-catalysts, fabrication of novel heterojunction constructions and factors influencing the photocatalytic process for dynamic H2 production have been discussed. In the mainstream, recent developments in TiO2 and g-C3 N4 based photo-catalysts and their potential for H2 production are extensively studied. The improvements have been classified as strategies to improve different factors of photocatalytic water splitting such as Z-scheme systems and influence of operating parameters such as band gap, morphology, temperature, light intensity, oxygen vacancies, pH, and sacrificial reagents. Moreover, thermodynamics for selective photocatalytic H2 production are critically discussed. The advances in photo-reactors and their role to provide more light distribution and surface area contact between catalyst and light were systematically described. By applying the optimum operating parameters and new engineering approach on photoreactor, the efficiency of semiconductor photocatalysts for H2 production can be enhanced. The future research and perspectives for photocatalytic water splitting were also suggested. Highlights: Strategies to improve efficiency of photocatalytic H2 evolutions. Thermodynamic, mass transfer and selectivity of solar H2 production. Advances in TiO2, g-C3 N4 and their heterojunctions for selective H2 evolution. Morphology, band structure, pH, temperature and charges separation for H2 yield. Advances in photocatalytic reactors and sacrificial reagents for H2 evolution.